MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA MELALUI PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) - Junaidi Junaidi; Taufiq Taufiq; Khairun Nisa (Universitas Jabal Ghafur, 2022)
The purpose of this research was conducted to determine the improvement of students critical thinking skills who received learning with a cooperative model of Think Pair Share (TPS) type with students who were taught conventional methods. This research was a quasi-experimental research with a pretest-posttest control group design. The population in this study were all eighth grade students of SMP Negeri 1 Mutiara. While the sample consisted of two classes, namely class VIII-6 and VIII-7 (experimental class and control class) which were taken by random sampling. The instrument used in this research is in the form of critical thinking ability test questions. Data were analyzed by SPSS-assisted t-test at a significant level of 0.05 after the test prerequisites were met. The results showed that the improvement in critical thinking skills of students who received learning with the Think Pair Share (TPS) cooperative model was better than students who received conventional learning. Keywords: Think Pair Share, critical thinking skills and conventional learning.Keywords: Think Pair Share, Critical Thinking Skills and Conventional Learning